Who are you? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
If we were to judge by the photographs sent in with this survey, there are two outstanding images of the typical Spore reader.One is of one or more people, equally men and women it seems, working in a field, tending crops and animals, or running...